Answer:
The Answer is: y - 3 = 3/2(x - 1)
Step-by-step explanation:
Given Points: (1, 3) and (-3, -3)
Find the slope m:
m = y - y1 / (x - x1)
m = 3 - (-3) / (1 - (-3))
m = 3 + 3 / 1 + 3
m = 6 / 4 = 3/2
Use the point slope form and point (1, 3):
y - y1 = m(x - x1)
y - 3 = 3/2(x - 1)
Hope this helps! Have an Awesome day!! :-)
1/2, 4/8, etc. Because they all equal to one half. <span />
Discriminant = square root (b^2 -4*a*c)
square root (64 -4*1*12) =
square root (16) =
4
Therefore it has 2 rational soltions
Answer:
sorry i can solve questions of level seven maybe I can help you with something else
Step-by-step explanation:
thank you!!!